The Effect of Job Engagement on Employee Performance with Employee Loyalty and Turnover Intention as a Variable Mediating at One of Manufacturing Company in Semarang City - Muhammad Ricza Irhamni; Lukmanul Hakim; Khairunnisak Khairunnisak; Bimo Suryo Wicaksono (Universitas Wahid Hasyim Semarang, 2022)
Abstract The purpose of this study is to examine and Analyze the effect of job engagement on employee performance with employee loyalty and turnover intention as a mediating variable at one of manufacturing company (musical instrument furniture, wood working and plastic injection) located in the industrial area of Wijaya Kusuma, Semarang, Central Java. The sample technique used is random sampling by using questionnaires and was distributed to 120 respondents consisting of contract employees with a minimum working period is 3 months, with returned data as many 117 questionnaires, and which later was proceeding as many 113 questionnaires. The data is then processed and analyzed using SEM (Structural Equation Modeling) which is operated by AMOS. The result of this study was found there is a significant effect between job engagement on employee performance; there is also a significant effect between job engagement on employee loyalty; then there is a significant effect between job engagement on turnover intention; then there is a significant effect between employee loyalty on employee performance; and in addition, there is a significant effect between turnover intention on employee performance. The findings are discussed in the light of previous evidence, and the implications can be used for the company.Key word :Job Engagement;Employee Performance; Employee Loyalty; Turnover Intention and Manufacturing Company